RELATIONSHIP BETWEEN THE EUROPEAN COURT OF HUMAN RIGHTS AND THE COURT OF JUSTICE OF THE EU IN THE FIELD OF HUMAN RIGHTS PROTECTION - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper deals with the issue of the relationship between two European courts – the European Court of Human Rights and the Court of Justice of the EU in cases of human rights protection. They represent two important international - European, instances for the protection of human rights, whose jurisdiction in relation to a large number of human rights overlaps. It is therefore important to analyse to what extent one respects the jurisprudence and positions of the other. Although neither of these two courts is based on the principles of case law, their jurisprudence is of great importance for the correct implementation of the legal sources that protect human rights in the Council of Europe and the European Union. Until the EU accedes to the European Convention on Human Rights, this will be the relationship between two completely separate courts, established in separate legal systems, but with strong interaction between them.